Analisis Strategi Manajemen Operasional Pada Coffee Shop di Kota Tarakan: Studi Kasus Bekawan Coffee, Terace Coffee, Bius Coffee, Dan Lain Coffee (Analysis of Operational Management Strategy in Coffee Shops in Tarakan City: Case Study of Bekawan Coffee, Terace Coffee, Bius Coffee, And Laan Coffee) - Ferawati Usman; Tinik Sugiati; Adhy Satya Pratama; Leopold Pratama Tangdikanan (CV. ITTC INDONESIA, 2026)
The rapid growth of coffee shops in Indonesia, particularly in Tarakan City, reflects significant changes in modern lifestyle, where coffee shops have evolved into social spaces and symbols of lifestyle identity. However, this growth has not been fully accompanied by the optimal achievement of visitor targets among business operators. This study aims to analyze operational management strategies and evaluate their effectiveness in four coffee shops in Tarakan City, namely Bekawan Coffee, Terace Coffee, Bius Coffee, and Lain Coffee. This research employs a mixed-method approach, combining qualitative and quantitative techniques. The population includes business actors and customers, with a total sample of 120 respondents selected using purposive sampling. Data collection was conducted through structured questionnaires, in-depth interviews, and direct observations. Data analysis utilized descriptive statistics based on a Likert scale and thematic analysis to strengthen the interpretation of findings. The results indicate that the operational management strategies implemented across the four coffee shops fall within good to very good categories, with each coffee shop demonstrating distinct strengths across operational dimensions. Nevertheless, a gap remains between targeted and actual visitor numbers, suggesting that operational effectiveness has not fully translated into market performance. Therefore, stronger integration between operational strategies, marketing strategies, positioning, and customer experience enhancement is required to achieve sustainable competitive advantage.